2019
DOI: 10.3390/app9091881
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue on “Side Channel Attacks”

Abstract: Cryptosystems are widely used in a growing number of embedded applications, such as smart cards, smart phones, Internet of Things (IoT) devices, and so on [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…For example, a SCA can be carried out on the power consumption, the sound that the device can emit, or even on the electromagnetic (EM) emissions. Currently, these security threats are serious problems for IoT systems, which are increasingly present in our daily lives, especially in the medical field [3]. Sangodovin et al [4] showed that information about IoT devices and FPGA modules can be collected from a distance of about 200 m outdoors through side channel EM signal leakage.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a SCA can be carried out on the power consumption, the sound that the device can emit, or even on the electromagnetic (EM) emissions. Currently, these security threats are serious problems for IoT systems, which are increasingly present in our daily lives, especially in the medical field [3]. Sangodovin et al [4] showed that information about IoT devices and FPGA modules can be collected from a distance of about 200 m outdoors through side channel EM signal leakage.…”
Section: Introductionmentioning
confidence: 99%
“…However, less robust solutions are seen among research communities associated with side-channel attacks. The prime origination point of a side-channel attack is the leakage of information related to power, light, sound, electromagnetic signal, and timing [13,14]. Being a passive attack, such an attack can break through the potential security system even if it is secured by brute force [15].…”
Section: Introductionmentioning
confidence: 99%